Agronomic studies in cymbopogons - a review - V P Singh, P P Singh, K Singh, S K Kothari, D V Singh, V P (Journal of Spices and Aromatic Crops, 2000)
Research on ’agronomic aspects of cymbopogons, Java citronella (Cymbopogon winterianus), palmarosa (C. martinii) and lemongrass (C. flexuosus) with respect to soil and climatic conditions, propogation, manures and fertilizers, irrigation, weed control and harvesting schedules to manIpulate then Yleld potential and quality of produce has been reviewed.